Clinical characteristics and outcomes for patients with an initial emergency presentation of malignancy: A 15 month audit of patient level data. Issue 1 (February 2015) - Savage, Philip; Sharkey, Rachel; Kua, Teresa; Papanastasopoulos, Panagiotis; McDonald-Burrows, Zoe; Hassan, Shazalia; Probst, Fay; Sanders, Ali; Millington, Hugh
Highlights Late diagnosis and emergency presentation of cancer patients remains a frequent event. Lung, colorectal and CNS cancers are the most common diagnoses. Emergency presentations patients are generally older than average. AOS services help expedite diagnosis and improve initial management.